90 Years’ Anniversary of Valentin I. Gryschenko (27.11.1928 – 03.01.2011) - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2018; 28(4):358-359